2015
DOI: 10.1371/journal.ppat.1005108
|View full text |Cite
|
Sign up to set email alerts
|

Goblet Cell Derived RELM-β Recruits CD4+ T Cells during Infectious Colitis to Promote Protective Intestinal Epithelial Cell Proliferation

Abstract: Enterohemorrhagic Escherichia coli and related food and waterborne pathogens pose significant threats to human health. These attaching/effacing microbes infect the apical surface of intestinal epithelial cells (IEC), causing severe diarrheal disease. Colonizing the intestinal luminal surface helps segregate these microbes from most host inflammatory responses. Based on studies using Citrobacter rodentium, a related mouse pathogen, we speculate that hosts rely on immune-mediated changes in IEC, including goblet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
79
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(84 citation statements)
references
References 51 publications
5
79
0
Order By: Relevance
“…This is consistent with the salt and pH sensitivity of other antimicrobial peptides (21) and likely reflects the fact that such antibacterial proteins have evolved to function in the acidic, low-salt environment that is present in the mucus layer (22). The requirement for these specialized conditions might also explain why RELMβ was previously reported to lack antibacterial activity (12). (14) showing the N-terminal α-helix and the C-terminal β-sheet with its aromatic residues.…”
Section: Resultssupporting
confidence: 78%
See 3 more Smart Citations
“…This is consistent with the salt and pH sensitivity of other antimicrobial peptides (21) and likely reflects the fact that such antibacterial proteins have evolved to function in the acidic, low-salt environment that is present in the mucus layer (22). The requirement for these specialized conditions might also explain why RELMβ was previously reported to lack antibacterial activity (12). (14) showing the N-terminal α-helix and the C-terminal β-sheet with its aromatic residues.…”
Section: Resultssupporting
confidence: 78%
“…S5B) and showed that C. rodentium infection led to higher numbers of tissue-associated bacteria in the absence of RELMβ (Fig. S5C), as previously reported (12).…”
Section: Relmβ Limits Entry Of Gram-negative Bacteria Into the Colon supporting
confidence: 87%
See 2 more Smart Citations
“…Additional comparisons of wild-type and IL-17A-deficient animals found that mice lacking IL-17A had significantly reduced fecal IgA levels both before and after infection, consistent with a role for IL-17 in inducing expression of the poly-Ig receptor that transports IgA from the serum into the intestinal lumen (15). IL-17A-deficient mice also had lower levels of mRNA encoding ␤-defensin-1, and IL-17RA-deficient mice had lower levels of mRNAs for resistin-like molecule ␤ (RELM-␤), serum amyloid A1 (Saa1), and serum amyloid A2 (Saa2), all proteins with potential antimicrobial and immunoregulatory functions (16)(17)(18)(19)(20).…”
Section: Cd197mentioning
confidence: 99%